A Multidimensional Path Analysis of Digital Transformation in Fujian's Manufacturing Sector - Luo, Mei (Pacific International Journal, 2025)
This study explores the multidimensional paths of digital transformation in Fujian’s manufacturing sector, focusing on two contrasting case studies: Zhangzhou Sanbao Group, a traditional heavy industry player, and ABB Xiamen Industrial Center, a leader in automation and electrification. The research investigates the interplay of technological, organizational, and policy factors that shape digital transformation processes. The sudy dicusses the technological advancements, organizational changes, and policy frameworks influencing these firms, to identify key enablers and barriers to digital adoption. The findings suggest that while large corporations benefit from advanced technologies and supportive policies, SMEs face significant challenges due to high adoption costs and limited access to cutting-edge solutions. The study provides insights for policymakers and business leaders on how to create a conducive environment for digital transformation, emphasizing the need for a holistic, integrated approach to overcoming barriers and fostering sustainable growth.